1984
DOI: 10.1007/bf00275654
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-anti-insulin complexes in diabetic women and their neonates

Abstract: It is known that insulin does not cross placenta, whereas maternal anti-insulin antibodies do. We have therefore investigated insulin antibodies and insulin-anti-insulin complexes both in pregnant diabetic women during pregnancy and in umbilical cord blood from their new-born infants. Forty-seven diabetic pregnant women and 23 new-born-infants of these diabetic women were studied. All the pregnant patients were studied at the end of pregnancy and in 27, at least on one other occasion during pregnancy. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Insulin autoantibodies are known to occur spontaneously in patients without a prior history of insulin injections, and furthermore, insulin-binding antibodies frequently occur before the onset of type I diabetes (7,(17)(18)(19). Wilkin et al (8) reported that 38% of newly diagnosed type I diabetic subjects and 47% of their unaffected identical twins had insulinbinding autoantibodies.…”
Section: Resultsmentioning
confidence: 98%
“…Insulin autoantibodies are known to occur spontaneously in patients without a prior history of insulin injections, and furthermore, insulin-binding antibodies frequently occur before the onset of type I diabetes (7,(17)(18)(19). Wilkin et al (8) reported that 38% of newly diagnosed type I diabetic subjects and 47% of their unaffected identical twins had insulinbinding autoantibodies.…”
Section: Resultsmentioning
confidence: 98%
“…Such bound insulin may interfere with fetal insulinglucose homeostasis (2). GDM provides an opportunity to study women without previous exposure to insulin.…”
mentioning
confidence: 99%
“…It has been proposed that IAs may induce abnormal insulin secretion and pancreatic insulitis in the fetus and newborn infant. Insulin-IA-complexes may be detected in the circulation of newborn infants; previously, these were thought to play a role in neonatal hypoglycemia [12]. More recently, Dozio et al [14] found no correlation between IAs and neonatal events.…”
Section: Transplacental Transfer Of Type 1 Diabetes-associated Antibomentioning
confidence: 97%
“…It has been shown that IA levels in women with type 1 diabetes remain quite stable during pregnancy [11,12] or decrease only slightly toward term [13,14]. At the time of delivery, it has been shown that around 74% to 90% of mothers with type 1 diabetes are IA-positive [15,16].…”
Section: Type 1 Diabetes-associated Antibodies During Pregnancymentioning
confidence: 98%